Evaluate \[\int {\sqrt {1 + {y^2}} \cdot 2ydy} \]
A) \[I = \dfrac{2}{3}{\left( {1 + {y^2}} \right)^{3/2}} + C\]
B) \[I = \dfrac{2}{5}{\left( {1 - {y^2}} \right)^{3/2}} + C\]
C) \[I = \dfrac{2}{3}{\left( {1 - {y^2}} \right)^{3/2}} + C\]
D) None of these
Answer
Verified
454.8k+ views
Hint:
Here we will firstly substitute the equation inside the square root to some variable and find its differentiation. Then we will substitute the variable and its derivative in the given equation. Then we will use the concept of the integration to integrate the equation. Then we will put the actual value of the function in place of the substituted variable in the integrated equation to get final integration value.
Formula used:
We will use the formula of integration, \[\int {{x^n}dx = \dfrac{{{x^{n + 1}}}}{{n + 1}} + C} \], to solve the question.
Complete step by step solution:
Let \[I = \int {\sqrt {1 + {y^2}} \cdot 2ydy} \].
Let us now assume \[u = 1 + {y^2}\].
Now we will differentiate \[u\].
Differentiating both sides of the above equation, we get
\[ \Rightarrow du = 2y \cdot dy\]
Now substituting \[u = 1 + {y^2}\] and \[du = 2y \cdot dy\] in \[I = \int {\sqrt {1 + {y^2}} \cdot 2ydy} \], we get
\[ \Rightarrow I = \int {{u^{\dfrac{1}{2}}}} du\]
Integrating the terms using the formula \[\int {{x^n}dx = \dfrac{{{x^{n + 1}}}}{{n + 1}} + C} \], we get
\[ \Rightarrow I = \dfrac{{{u^{\dfrac{1}{2} + 1}}}}{{\dfrac{1}{2} + 1}} + C\]
Adding the terms in the denominator and the exponent, we get
\[ \Rightarrow I = \dfrac{2}{3}{u^{\dfrac{3}{2}}} + C\]
Now we will put the value of \[u\] in the above equation to get the value of the integration in terms of the \[y\]. Therefore, we get
\[ \Rightarrow I = \dfrac{2}{3}{\left( {1 + {y^2}} \right)^{\dfrac{3}{2}}} + C\]
Hence the value of the \[\int {\sqrt {1 + {y^2}} \cdot 2ydy} \] is equal to \[I = \dfrac{2}{3}{\left( {1 + {y^2}} \right)^{3/2}} + C\].
So, option A is the correct option.
Note:
Here we should note that the value of the substitution must be done accordingly. In the integration with the limits we also have to convert the limits according to the substitution but in our case it's simple integration without limits of the integration. Differentiation is the opposite of the integration i.e. differentiation of the integration is equal to the value of the function or vice versa. We have to remember to put the constant term \[C\] after the integration of an equation.
Here we will firstly substitute the equation inside the square root to some variable and find its differentiation. Then we will substitute the variable and its derivative in the given equation. Then we will use the concept of the integration to integrate the equation. Then we will put the actual value of the function in place of the substituted variable in the integrated equation to get final integration value.
Formula used:
We will use the formula of integration, \[\int {{x^n}dx = \dfrac{{{x^{n + 1}}}}{{n + 1}} + C} \], to solve the question.
Complete step by step solution:
Let \[I = \int {\sqrt {1 + {y^2}} \cdot 2ydy} \].
Let us now assume \[u = 1 + {y^2}\].
Now we will differentiate \[u\].
Differentiating both sides of the above equation, we get
\[ \Rightarrow du = 2y \cdot dy\]
Now substituting \[u = 1 + {y^2}\] and \[du = 2y \cdot dy\] in \[I = \int {\sqrt {1 + {y^2}} \cdot 2ydy} \], we get
\[ \Rightarrow I = \int {{u^{\dfrac{1}{2}}}} du\]
Integrating the terms using the formula \[\int {{x^n}dx = \dfrac{{{x^{n + 1}}}}{{n + 1}} + C} \], we get
\[ \Rightarrow I = \dfrac{{{u^{\dfrac{1}{2} + 1}}}}{{\dfrac{1}{2} + 1}} + C\]
Adding the terms in the denominator and the exponent, we get
\[ \Rightarrow I = \dfrac{2}{3}{u^{\dfrac{3}{2}}} + C\]
Now we will put the value of \[u\] in the above equation to get the value of the integration in terms of the \[y\]. Therefore, we get
\[ \Rightarrow I = \dfrac{2}{3}{\left( {1 + {y^2}} \right)^{\dfrac{3}{2}}} + C\]
Hence the value of the \[\int {\sqrt {1 + {y^2}} \cdot 2ydy} \] is equal to \[I = \dfrac{2}{3}{\left( {1 + {y^2}} \right)^{3/2}} + C\].
So, option A is the correct option.
Note:
Here we should note that the value of the substitution must be done accordingly. In the integration with the limits we also have to convert the limits according to the substitution but in our case it's simple integration without limits of the integration. Differentiation is the opposite of the integration i.e. differentiation of the integration is equal to the value of the function or vice versa. We have to remember to put the constant term \[C\] after the integration of an equation.
Recently Updated Pages
Master Class 12 Economics: Engaging Questions & Answers for Success
Master Class 12 Maths: Engaging Questions & Answers for Success
Master Class 12 Biology: Engaging Questions & Answers for Success
Master Class 12 Physics: Engaging Questions & Answers for Success
Master Class 12 Business Studies: Engaging Questions & Answers for Success
Master Class 12 English: Engaging Questions & Answers for Success
Trending doubts
Which are the Top 10 Largest Countries of the World?
Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE
Draw a labelled sketch of the human eye class 12 physics CBSE
What is the Full Form of PVC, PET, HDPE, LDPE, PP and PS ?
What is a transformer Explain the principle construction class 12 physics CBSE
What are the major means of transport Explain each class 12 social science CBSE